Population structure, soil characteristics and carbon stock of the regenerating banj oak forests in Almora, Central Himalaya. Issue 3 (3rd July 2019) - Verma, Abhishek K.; Garkoti, Satish Chandra
Abstract: The present study is aimed to study regeneration status, population structure, soil characteristics and carbon stock of seven regenerating banj oak ( Quercus leucotrichophora ) forests in the central Himalaya. The phytosociological study was done by using ten 10 m × 10 m quadrat at each site. Biomass and carbon stock of trees were calculated by using regression equations. Soil samples were collected from three depths (0–10, 10–20 and 20–30 cm) by using soil corer. The tree density of two most dominant species of the study sites i.e. banj oak and pine ( Pinus roxburghii ) varied from 260–1200 trees ha −1 and 90–300 trees ha −1, respectively. Whereas, basal area of banj oak and pine varied between 5.5–21.0 m 2 ha −1 and 6.4–26.0 m 2 ha −1, respectively. Density-diameter curve indicated the increasing population of banj oak while declining pine in all the sites. Carbon density of the banj oak was found between 46.96–167.36 Mg ha −1 and in pine it was 17.18–72.95 Mg ha −1 . Soil nutrient (especially carbon and nitrogen) improved with increase in density and basal area of forests. Additionally, substantial amount of carbon stored by these trees makes them viable for the region. Thus, identification and conservation of such forests are recommended.